Manifestation of anharmonicities in terms of phonon modes' energy and lifetime in multiwall carbon nanotubes. (January 2021) - Sharma, Meenu; Rani, Sonam; Pathak, Devesh K.; Bhatia, Ravi; Kumar, Rajesh; Sameera, I.
Abstract: The temperature dependent Raman spectromicroscopic study has been carried out to investigate anharmonic effects in multiwall carbon nanotubes (MWCNT). The micro-Raman scattering experiments have been carried out over a wide temperature range of 173–723 K to analyze manifestation of various MWCNT Raman modes' energy and lifetimes. The experimental results indicated non-linear shifts in the peak position of Raman D- and G-bands with temperature. Phonon softening of Raman modes was observed over a wide temperature range from 273–648 K, and hardening of Raman modes was noticed in both, high- and low-, temperature regimes. Temperature dependent shift of the G-peak has been explained on the basis of anharmonic properties of graphite lattice. Contributions from true-anharmonic and quasi-harmonic parts in shifting the G-peak position have also been explained. Interestingly, the variation of peak width for G-peak of MWCNT appeared to be nearly independent of temperature, likely due to the competing effects from the electron-phonon coupling and anharmonic contributions in the observed temperature range. Graphical abstract: Image 1 Highlights: Analyzed phonon-anharmonicities of MWCNT by temperature-dependent Raman-spectra. Correlation of experimental results with the theoretical models was established. Results indicate dominance of anharmonic contributions over quasi-harmonicity. Peak width for G-peak of MWCNT found to be independent of temperature. Electron-phonon coupling and anharmonic effects found to dictate the G-peak width.